A dual-responsive luminescent sensor based on a water-stable Cd(ii)-MOF for the highly selective and sensitive detection of acetylacetone and Cr2O72− in aqueous solutions. Issue 7 (30th January 2020) - Yang, Ying-Jie; Li, Yue-Hua; Liu, Dong; Cui, Guang-Hua
Abstract : Two water-stable cadmium(ii ) MOFs were synthesized and characterized. 1 is the first dual-function Cd(ii )-MOF luminescent sensor for sensing acetylacetone and Cr2 O7 2− in aqueous solution with high sensitivity and selectivity and good recyclability. Abstract : Two new water-stable cadmium(ii )-metal organic frameworks (MOFs), namely [Cd2 (L1)(1, 4-NDC)2 ] n (1 ) and [Cd(L2)(1, 4-NDC)] n (2 ) (L1 = 1, 4-bis(benzimidazol-1-yl)-2-butylene, L2 = 1, 4-bis(2-methylbenzimidazol-1-yl)-2-butylene and 1, 4-H2 NDC = 1, 4-naphthalenedicarboxylic acid), were synthesized and characterized. 1 exhibits an unusual 3D framework with the Schläfli symbol of {4 2 ·5·6 2 ·7}{4 2 ·5 2 ·7 2 }{4 2 ·5 3 ·6 2 ·7 3 }2, and 2 is a classical sqc6 network. 1 and 2 display excellent pH and water stability, and the integrity of the frameworks was well maintained at different pH values (pH = 3–13) and after long-term water treatment. 1 is the first dual-function luminescent sensor for sensing acetylacetone and Cr2 O7 2− in aqueous solutions with high sensitivity, selectivity and excellent recyclability. This material is an excellent dual-responsive recyclable luminescent sensor.